Strategi Membangun Budaya Organisasi yang Inovatif dalam Menghadapi Era Digital - Manurung, Febriani; Hasibuan, Wildan Anshori; Ananda, Fauzi; Nisa, Mahmudan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze effective strategies for building an innovative organizational culture to face challenges in the digital era. The research method used is a qualitative study with a case study approach in technology companies in Indonesia. Data were collected through in-depth interviews and company document analysis. The results show that the implementation of transformational leadership, technology-based human resource development, and the creation of a collaborative work environment are key strategies in fostering an innovative culture. These findings are expected to serve as a reference for companies in adapting to digital developments.